Study of Materials’ Impact Properties for Arctic Marine Structures - Xue, Hui; Khawaja, Hassan Abbas; Moatamedi, Mojtaba; Kwon, Young; Sun, Zhiheng (2016)
Presentation held at The International Conference of Multiphysics (arranged by The International Conference of Multiphysics) in Zurich, 08.12.16 - 09.12.16. It is well understood that sea ice is one of the biggest problems for the safety and reliability of ships and marine structures operating in the Arctic. Specially designed ships, also known as ‘icebreakers’, are usually used to clear ice to make way for merchant and cruise ships. Even then, the ship’s staff must be extremely careful with speed and steering. Heavy impacts of ice result in fatigue and damage in the hull, which may lead to serious damage to the integrity of the ship. This work is to study materials that may be applied to the ship hull for providing an extra layer of protection. This study looks at the impact resistive properties of two different materials. The first material considered is carbon fiber reinforced polymer (CFRP). CFRP is proven for its strength to weight ratio and already in use in many applications, such as aviation industry, professional sports, etc. The second material is a non-toxic material ‘SK One Component Polyurethane (SOCP)’ developed by China Institute of Water Resources & Hydropower Research (IWHR). This material is light and can be applied as a coating. Also, this material has proven to have good abrasion resistance even in temperatures as low as -45°C. In this work, we plan to perform experimental and numerical analysis. In an experimental study, diabolo pellets of 0.5 g will be fired at a speed of 160 m/s on the samples of CFRP and SOCP using an airgun. The tests will be carried out on various thicknesses of materials and in a cold room where low temperature conditions can be reproduced. In the numerical study, simulations will be performed using ANSYS® Workbench simulation software. The study will reveal the impact resistive properties of the materials, which will help identify their application towards marine applications in the Arctic region.